Mit gutem Recht erinnern. Gedanken zur Änderung der rechtlichen Rahmenbedingungen des kulturellen Erbes in der digitalen Welt - Klimpel, Paul (Hamburg University Press, 2018)
The law, in particular copyright, has a major impact on what remains in collective memory of the great wealth of our cultural heritage. In the digital world where everything is copy and therefore - in the sense of copyright - reproduction, every use of the cultural heritage is also relevant under copyright law. On the other hand, we live in times of rapid media development and an abundance of information, images, films and texts. This is why the challenge of keeping the memory of our cultural heritage alive is all the greater. It is therefore a question of cultural self-assertion how the legal framework conditions for dealing with our cultural heritage are set. What cannot be found online will increasingly disappear. In this respect, the effects of an unbalanced copyright law that does not take sufficient account of cultural heritage can be dramatic. This book brings together various proposals and reflections on how to change the legal framework in order to increase the presence of copyrighted cultural heritage on the Internet. These proposals are written by experts from memory institutions, law and politics, and thus by authors who are well acquainted with the international framework conditions and copyright discourse in Germany.